2022
DOI: 10.1038/s41467-022-29155-1
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain projection to the basolateral amygdala encodes anxiety-like but not depression-like behaviors

Abstract: Anxiety disorders are complex diseases, and often co-occur with depression. It is as yet unclear if a common neural circuit controls anxiety-related behaviors in both anxiety-alone and comorbid conditions. Here, utilizing the chronic social defeat stress (CSDS) paradigm that induces singular or combined anxiety- and depressive-like phenotypes in mice, we show that a ventral tegmental area (VTA) dopamine circuit projecting to the basolateral amygdala (BLA) selectively controls anxiety- but not depression-like b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 64 publications
6
68
0
1
Order By: Relevance
“…Mice exposed to the UCMS protocol and the isolation period exhibited signs of anxiety-like behavior, as indicated by reduced time in the open arm of the elevated plus maze (Figure 1C). The stress components did induce social impairment, which is a function associated with a depressive phenotype in mice [29]. Social interaction was tested for social approach (Figure 1D) based on interaction time exploring an unfamiliar mouse relative to an empty carrier and for social memory (Figure 1E) based on preference for exploring the first now familiar mouse relative to a subsequently introduced unfamiliar mouse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice exposed to the UCMS protocol and the isolation period exhibited signs of anxiety-like behavior, as indicated by reduced time in the open arm of the elevated plus maze (Figure 1C). The stress components did induce social impairment, which is a function associated with a depressive phenotype in mice [29]. Social interaction was tested for social approach (Figure 1D) based on interaction time exploring an unfamiliar mouse relative to an empty carrier and for social memory (Figure 1E) based on preference for exploring the first now familiar mouse relative to a subsequently introduced unfamiliar mouse.…”
Section: Resultsmentioning
confidence: 99%
“…The current experimental design induced anxiety without evidence of depressive signs that have been differentiated based on social interaction in mice [29]. Social function is an important factor in mood disorders after TBI [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are important controls which should be considered when assessing fiber photometry data, to prevent the influence of motion artifacts on the signal. In addition to the 470-nm GCaMP channel, we also recorded fluorescence intensity from a 415-nm channel as is standard for fiber photometry 52 56 . The 415-nm channel is consistent with the isosbestic point of GCaMP7f 33 ; therefore the resulting fluorescence intensity recorded in response to this wavelength is considered to be independent of calcium binding.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our behavioral results, a previous study has shown that partial Fzd6 knockdown in the brain of rats induced anhedonic responses and anxiety, such as decreased sucrose preference, suppressed feeding, and altered performance in the EPM ( Voleti et al, 2012 ). In a most recent paper, Morel et al (2022) utilized the same paradigm CSDS to induce anxiety- and depressive-like phenotypes, and the results showed that the ventral tegmental area (VTA) to basolateral amygdala (BLA) dopamine projection is an important circuit mechanism for anxiety-like behaviors and anxiety-depressive comorbid conditions, but not for depressive-like behaviors in mice. Thus, the behavioral alterations observed in the present study further demonstrated the functional role of rs61753730 in depression, which may attribute to a VTA→BLA dopamine neural circuit.…”
Section: Discussionmentioning
confidence: 99%